Clinical nurses' moral courage and related factors: an empowerment perspective - Kaili Hu; Juan Liu; Lisi Zhu; Yanrong Zhou (BMC, 2022)
Abstract Background Moral courage as part of the moral competence of nurses has received increasing attention. Determination of the factors affecting moral courage is important in improving the quality of care. The purpose of this study was to investigate moral courage and related factors among frontline nurses from an empowerment perspective. Methods A cross-sectional study was conducted using data collection instruments comprising four main parts: the self-designed form of demographic characteristics, Conditions for Work Effectiveness II (CWEQ-II), Spreitzer's Psychological Empowerment Scale (PES) and Nurses' Moral Courage Scale (NMCS). Data were collected from 226 nurses in a tertiary hospital between February and March 2022 in Wuhan, the capital city of Hubei Province in central China. Descriptive statistics and multiple linear regression were used to analyze the data. Results The means of the total scores for the CWEQ-II, PES and the NMCS were 3.52 (SD = 0.69), 3.85 (SD = 0.53) and 3.90 (SD = 0.67), respectively. All the dimensions and the total scores of the CWEQ-II and PES were significantly correlated with the NMCS (p < 0.001). According to the multivariate stepwise regression analysis, CWEQ-II and PES were determined to be factors affecting NMCS. These variables explained 35.9% of the total variance in the moral courage scores of nurses. Conclusion The level of moral courage among nurses is above average. Structural empowerment and psychological empowerment were the key factors affecting the promotion of moral courage. Hospital and organizational administrations should be conscious of the role of attach structural empowerment and psychological empowerment in the nursing workplace in increasing moral courage.